Avalia????o do impacto de ecoinova????es: o caso da tecnologia de biodigestores aplicada na agroind??stria processadora de mandioca do estado do Paran?? - Jesus, Marco Antonio Sampaio de (2015)
The negative externalities caused by production activities to satisfy the consumption needs impact directly on the natural environment, for example, the emission of greenhouse gases and pollution of soil and water, requiring new approaches to decision-making processes in organizations. Among these approaches are incorporating innovations that provide reduced environmental impacts, also called eco-innovations, and the adoption of models that assess comprehensively, integrated and in different perspectives the overall performance of these innovations. Considering that the object of this research is the eco-innovation 'biodigester technology' and the research field are the processing of cassava industries in State of Paran??, this multicase study included an extensive literature review to propose a specific set of indicators to assess the overall impact caused by the eco-innovation cited, covering the classic dimensions of sustainable development (environmental, social and economic) as well as other dimensions defined for the model used (training of human resources, institutional development, introducing innovation, unexpected/unwanted occurrences and characteristics of environmental management). This set of indicators was incorporated into the INOVA-tec System Model (Jesus-Hitzschky, 2007) developed by a researcher at the Brazilian Agricultural Research (Embrapa), setting up a new model called INOVA-tec System Modified. The primary data were processed in the new model and after analysis of the results it was evident that the technology object of this research has a favorable scenario for its spread, but the performance indicators are still low. Then were then presented suggestions for improvement to optimize the overall impact of the technology and at the end, it is recommended that the model proposed in this study be applied to other activities of the agricultural industry in order to validate and improve it??s theoretical contribution.